Investment in African manufacturing a microeconomic analysis - Söderbom, Måns (Nationalekonomiska Inst., 2000)
Thesis (Ph. D.)--Göteborgs universitet, 2000.
Keywords: Investments -- Africa -- Case studies; Manufacturing industries -- Africa -- Finance -- Case studies; Mikroökonomie; Investition; Mikroökonomisches Modell; Investitionsverhalten; Industriebetrieb; Afrika; Subsaharisches Afrika; Fallstudiensammlung; Hochschulschrift